AB0273 Efficacy and safety of add-on golimumab treatment in patients with rheumatoid arthritis receiving concomitant methotrexate or leflunomide. (23rd January 2014) - Wollenhaupt, J.; Alonso-Ruiz, A.; Spieler, W.; Beier, J.; Molina, J.; Yao, R.; Govoni, M.; Vastesaeger, N.; Weng, H. H.
Abstract : Background: Current labeling requires rheumatoid arthritis (RA) patients receiving golimumab (GLM) to receive concomitant methotrexate (MTX), and most studies have investigated GLM on the background of MTX treatment. Limited information is available regarding GLM as add-on therapy to disease-modifying antirheumatic drugs (DMARD) such as leflunomide (LEF). Objectives: To evaluate the effectiveness and safety of GLM as add-on therapy in biologic-naïve patients with RA receiving concomitant MTX or LEF in clinical settings. Methods: GO-MORE was an open-label, multinational, prospective study in biologic-naïve patients with active RA (DAS28-ESR ≥3.2). Patients received 50-mg SC GLM once monthly for 6 months. The primary outcome was the percentage of patients with good or moderate EULAR DAS28-ESR response at 6 months. Remission (DAS28-ESR <2.6) and minimal or no functional impairment (Health Assessment Questionnaire-Disability Index [HAQ-DI] ≤0.5) were also assessed. Treatment effects were evaluated with chi-square tests. Post hoc analyses evaluated outcomes in patients who received concomitant MTX or concomitant LEF. Results: Patients receiving GLM with concomitant MTX (alone or with other DMARDs) or GLM with concomitant LEF (with no other DMARDs) accounted for 81.2% (2663/3280) and 9.3% (303/3270) of the total study population, respectively. The concomitant MTX and LEF subgroups had comparable baseline disease characteristics, including mean DAS28-ESR (5.43 and 5.25, respectively), DAS28-CRP (5.99 and 5.79, respectively), and HAQ-DI (1.44 and 1.36, respectively). These values were similar to the baseline means of the overall population. At month 6, similarly high EULAR response rates were noted in the GLM with concomitant MTX (85%) and GLM with concomitant LEF (81%) subgroups (Table ). Similar EULAR responses were also observed in patients receiving GLM+MTX without other DMARDs (83%) and GLM+MTX+LEF without other DMARDs (78%). Serious treatment-emergent adverse events (TEAEs) occurred in 5.1% (136/2656) of the concomitant MTX subgroup and 6.8% (21/309) of the LEF subgroup. There were 5 (0.19%) and 0 deaths in the concomitant MTX and LEF subgroups, respectively. Conclusions: Overall, add-on SC GLM therapy was highly efficacious with concomitant MTX or LEF in patients with active RA despite DMARD therapy. Safety profiles were consistent with those of previous studies of GLM. Disclosure of Interest: J. Wollenhaupt Consultant for: Abbott, Biotest, BMS, Chugai, MSD, Medac, Merck, MSD, Pfizer, Roche, and UCB., Speakers bureau: Abbott, Biotest, BMS, Chugai, MSD, Medac, Merck, MSD, Pfizer, Roche, and UCB., A. Alonso-Ruiz: None Declared, W. Spieler: None Declared, J. Beier: None Declared, J. Molina: None Declared, R. Yao Employee of: Merck, M. Govoni Employee of: Merck, N. Vastesaeger Employee of: Merck, H. Weng Employee of: Merck